Catastrophe Losses and Insurance: การประกันความเสียหายจากภัยพิบัติ - Preechametta, Arayah; Benyaapikul, Pornthep; Leawsakul, kuson (Journal of Applied Economics and Management Strategy, 2019)
บทคัดย่อ งานวิจัยนี้ได้ทำการวิเคราะห์เปรียบเทียบปัญหาและแนวทางปฏิบัติที่มีการใช้จริงของระบบประกันภัยพิบัติขนาดใหญ่ในต่างประเทศ โดยมีจุดมุ่งหมายในการเรียนรู้วิธีการกระจายความเสี่ยงจากภัยพิบัติเพื่อนำมาปรับใช้ได้อย่างมีประสิทธิภาพสำหรับประเทศไทยต่อไป งานวิจัยได้ทำการสำรวจองค์ความรู้จากกรณีศึกษาของต่างประเทศที่มีประสบการณ์จากภัยพิบัติครั้งใหญ่บ่อยครั้ง เช่น ญี่ปุ่น ตุรกี จีน และสหรัฐอเมริกา รวมทั้งวิเคราะห์ปัญหาและข้อจำกัดในการจัดการประกันภัยพิบัติ ซึ่งพบว่าปัญหาความล้มเหลวของระบบตลาดจากข้อจำกัดทางด้านอุปทานและอุปสงค์ และปัญหาวัฏจักรของการรับประกันภัยพิบัติ เป็นสาเหตุสำคัญที่ตลาดประกันภัยโดยเอกชนไม่สามารถทำหน้าที่ได้อย่างเต็มที่ นอกจากนี้งานวิจัยยังได้รวบรวมแนวทางที่รัฐจะสามารถเข้าไปมีบทบาทในการแก้ไขปัญหาเหล่านี้ ซึ่งจะขึ้นอยู่กับระดับความต้องการแทรกแซงของรัฐและบทบาทของตลาด และทำการเปรียบเทียบข้อดีข้อเสีย รวมทั้งปัญหาเชิงการจัดการที่อาจจะเกิดขึ้นในแต่ละแนวทาง ผลการศึกษาได้นำไปสู่ข้อเสนอแนวทางเบื้องต้นในการจัดตั้งกองทุนประกันภัยพิบัติโดยภาครัฐ ซึ่งจะเป็นกองทุนที่ทำหน้าที่เป็นผู้รับประกันภัยต่อ และข้อเสนอเกี่ยวกับรูปแบบโครงสร้างการบริหารกองทุนที่สนับสนุนการดำเนินการแก้ปัญหาร่วมกันระหว่างภาครัฐและเอกชนให้มีประสิทธิภาพมากขึ้น คำสำคัญ: การประกันภัยพิบัติ การบริหารความเสี่ยง ความล้มเหลวของระบบตลาดในกิจการประกันภัย ABSTRACT This research surveys the frontier of knowledge of the catastrophic insurance literature and reviews various policies implemented to efficiently diversify risks in many countries where a catastrophic natural disaster is waiting to happen. The study also reviews the sources of database and information systems in many best practice countries in order to recommend suitable catastrophic insurance and information management systems for Thailand. The study uses case studies of frequent catastrophic-hit countries such as Japan, Turkey, China, and the USA. The major problem regarding effective catastrophic insurance is the problem of market failure arising from supply and demand mismatches that lead to the problem of the cycle of catastrophic insurance. This causes market and private insurance companies to be unable to work effectively. The study also reviews the role of government in intervening and correcting market failure problems. Various forms of government interventions, depending on the degree of government involvement, are considered, and advantages and disadvantages are then compared. Potential management problems are also discussed. Based on the research findings, preliminary proposals to establish a catastrophic reinsurance fund are proposed, while fund details are issues for future research. Keywords: Catastrophic Insurance, Risk Management, Market Failure in Catastrophic Insurance